The Journey to Sustainable Digital Business Models: Embedding Twin Transformation for Long-Term Survival - Vester, Tara (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This PhD explores how organizations overcome resource constraints and develop dynamic capabilities within the Twin Transformation (TT) to move toward sustainable digital business models. TT—the convergence of digital and sustainability transformations—requires organizations to reshape their business models to stay resilient in an evolving landscape. Yet, as both TT and sustainable digital business models are still emerging concepts, the implications and necessary organizational adaptations remain unclear. The complexity of the TT, with its dilemmas and trade-offs, adds further challenges. This research investigates how internal and external dynamics influence TT adoption, and how organizations orchestrate resources and build capabilities to overcome barriers. Using a qualitative, process-oriented approach findings are expected to show that the TT must be approached as a fundamental organizational change, with similar constraints and capability challenges emerging across organizations. This study contributes to the discourse on TT, organizational change, and sustainable digital business model discourse, offering practical guidance to strengthen organizational resilience.